High-performance flame-retardant polymer electrolyte membrane as well as preparation method and application thereof

By using electrospinning technology and nanofire retardant in the lithium-ion battery electrolyte membrane, combined with the hot press bonding method of graphene oxide reinforcement layer, the existing battery electrolyte membrane has solved the problems of insufficient flame retardancy, ionic conductivity and mechanical properties, and the electrolyte membrane with high performance, versatility and green preparation process is achieved.

CN119890450APending Publication Date: 2025-04-25SHENZHEN NO 1 FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070799.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The liquid organic electrolyte used in existing lithium-ion batteries has problems such as poor thermal safety performance, flammability and limited electrochemical windows. The flame retardancy, ionic conductivity, mechanical properties of traditional polymer electrolyte membranes have not yet fully met the requirements of high-performance batteries.

Method used

By adding high ionic conductivity lithium salt and ionic liquid to the polymer solution for electrospinning, a high ionic conductivity base film was obtained, and then a flame retardant was coated on the base film, combining the synergistic effect of the nano-silicon-based flame retardant and the phosphorus-based flame retardant, the flame retardant performance was significantly improved. At the same time, the graphene oxide-containing polymer film layer prepared by casting the film is used as a reinforcement layer, and is combined with the base film by hot pressing, which significantly improves the mechanical properties of the electrolyte film.

Benefits of technology

It achieves high flame retardancy, high ionic conductivity and excellent mechanical properties, meets the requirements of high-performance batteries, and adopts green preparation technology, which is more environmentally friendly.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolyte membranes, and discloses a high-performance flame-retardant polymer electrolyte membrane as well as a preparation method and application thereof. The lithium salt with high ionic conductivity and the ionic liquid are added into the polymer solution for electrostatic spinning to obtain the base membrane with high ionic conductivity, then the base membrane is coated with the flame retardant, and through the synergistic effect of the nano silicon-based flame retardant and the phosphorus-based flame retardant, the flame retardant property is remarkably improved, and the service life is prolonged. And a polymer film layer which is prepared through film casting and contains graphene oxide is used as a reinforcing layer and is combined with the base film through hot pressing. The enhancement layer obviously improves the mechanical property of the electrolyte membrane, and realizes the synergistic effect of flame retardance and mechanical enhancement. The electrolyte membrane prepared by the invention has high flame retardance, high ionic conductivity and excellent mechanical properties, and can meet the requirements of high-performance batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolyte membranes, and in particular to a high-performance flame-retardant polymer electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Existing lithium-ion batteries mostly use liquid organic electrolytes, which have problems such as poor thermal safety, flammability and limited electrochemical window. The flame retardancy, ionic conductivity, and mechanical properties of traditional polymer electrolyte membranes have not yet fully met the requirements of high-performance batteries. In addition, the preparation process of polymer electrolyte membranes mostly uses toxic solvents and has poor environmental protection. Therefore, a new type of polymer electrolyte membrane with high performance, multifunctionality and green preparation process is urgently needed to solve the bottleneck problems of existing technologies. Summary of the invention

[0003] The purpose of the present invention is to provide a high-performance flame-retardant polymer electrolyte membrane and a preparation method and application thereof, so as to solve the problems of poor flame retardancy, ionic conductivity and mechanical properties of the existing polymer electrolyte membrane.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0006] Mixing a polymer material and a solvent to obtain a polymer solution; adding an ion conductive material to the polymer solution to obtain a spinning solution; electrospinning the spinning solution to obtain a base film; coating a flame retardant solution on the surface of the base film to obtain a flame retardant base film;

[0007] Mixing graphene oxide, polymer material and solvent to obtain a reinforcement layer solution; casting the reinforcement layer solution into a film to obtain a reinforcement film layer;

[0008] The flame-retardant base film and the reinforcement film layer are hot pressed to obtain a high-performance flame-retardant polymer electrolyte membrane.

[0009] Preferably, in the above method for preparing a high-performance flame-retardant polymer electrolyte membrane, the polymer material is independently one or more of polylactic acid, polyvinyl alcohol, and polyvinylidene fluoride.

[0010] Preferably, in the above method for preparing a high-performance flame-retardant polymer electrolyte membrane, the ion conductive material is a mixture of lithium salt and ionic liquid; the mass of the ion conductive material is 10-50% of the mass of the polymer solution.

[0011] Preferably, in the above-mentioned method for preparing a high-performance flame-retardant polymer electrolyte membrane, the conditions for electrospinning are: voltage of 10 to 20 kV; working distance of 12 to 20 cm; injection rate of 0.3 to 1 mL / h.

[0012] Preferably, in the above-mentioned method for preparing a high-performance flame-retardant polymer electrolyte membrane, the flame retardant in the flame retardant solution comprises a mixture of hexaphenoxy cyclotriphosphazene, trimethyl phosphate, and nano-silicon dioxide; the coating amount of the flame retardant in the coating flame retardant solution is 0.5-2 mg / cm 2 .

[0013] Preferably, in the above-mentioned method for preparing a high-performance flame-retardant polymer electrolyte membrane, the mass fraction of graphene oxide in the reinforcement layer solution is 5-10%; the mass fraction of the polymer material in the reinforcement layer solution is 8-15%.

[0014] Preferably, in the above method for preparing a high-performance flame-retardant polymer electrolyte membrane, the thickness of the reinforcement film layer is 10 to 20 μm.

[0015] Preferably, in the above-mentioned method for preparing a high-performance flame-retardant polymer electrolyte membrane, the temperature of the hot pressing is 80 to 150° C.; the pressure of the hot pressing is 0.5 to 2 MPa; and the time of the hot pressing is 10 to 60 min.

[0016] The invention also provides a high-performance flame-retardant polymer electrolyte membrane prepared by a method for preparing the high-performance flame-retardant polymer electrolyte membrane.

[0017] The present invention also provides an application of a high-performance flame-retardant polymer electrolyte membrane in a lithium-ion battery.

[0018] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention adds a lithium salt with high ionic conductivity and an ionic liquid to a polymer solution for electrostatic spinning to obtain a base film with high ionic conductivity, and then coats the base film with a flame retardant. The flame retardant is significantly improved by the synergistic effect of the nano-silicon-based flame retardant and the phosphorus-based flame retardant. The polymer film layer containing graphene oxide obtained by film casting is used as a reinforcement layer and combined with the base film by hot pressing. The reinforcement layer significantly improves the mechanical properties of the electrolyte membrane and achieves the synergistic effect of flame retardancy and mechanical reinforcement. The electrolyte membrane prepared by the present invention has high flame retardancy, high ionic conductivity and excellent mechanical properties, and can meet the requirements of high-performance batteries. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0021] Mixing a polymer material and a solvent to obtain a polymer solution; adding an ion conductive material to the polymer solution to obtain a spinning solution; electrospinning the spinning solution to obtain a base film; coating a flame retardant solution on the surface of the base film to obtain a flame retardant base film;

[0022] Mixing graphene oxide, polymer material and solvent to obtain a reinforcement layer solution; casting the reinforcement layer solution into a film to obtain a reinforcement film layer;

[0023] The flame-retardant base film and the reinforcement film layer are hot pressed to obtain a high-performance flame-retardant polymer electrolyte membrane.

[0024] In the present invention, the polymer material is independently preferably one or more of polylactic acid (PLA), polyvinyl alcohol (PVA), and polyvinylidene fluoride (PVDF), further preferably a mixture of PVA and PVDF, and more preferably a mixture of PVA and PVDF in a mass ratio of 3:7.

[0025] In the present invention, the molecular weight of the polylactic acid is preferably 50,000 to 200,000 g / mol, more preferably 80,000 to 120,000 g / mol, and more preferably 90,000 to 110,000 g / mol.

[0026] In the present invention, the molecular weight of the polyvinyl alcohol is preferably 10,000 to 200,000 g / mol, more preferably 80,000 to 150,000 g / mol, and more preferably 100,000 to 120,000 g / mol.

[0027] In the present invention, the molecular weight of the polyvinylidene fluoride is preferably 300,000 to 500,000 g / mol, more preferably 350,000 to 450,000 g / mol, and more preferably 400,000 to 450,000 g / mol.

[0028] In the present invention, the solvent is preferably N,N-dimethylformamide (DMF).

[0029] In the present invention, the mass fraction of the polymer material in the polymer solution is preferably 10 to 20%, more preferably 12 to 18%, and even more preferably 15%.

[0030] In the present invention, the ion conductive material is preferably a mixture of a lithium salt and an ionic liquid; the lithium salt is preferably LiPF6 or LiTFSI, and more preferably LiPF6; the ionic liquid is preferably 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]) or 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), and more preferably [EMIM][TFSI].

[0031] In the present invention, the mass of the ion conductive material is preferably 10 to 50% of the mass of the polymer solution, more preferably 20 to 50%, and even more preferably 30%.

[0032] In the present invention, the conditions for electrospinning are: the voltage is preferably 10-20 kV, more preferably 14-17 kV, and more preferably 15 kV; the working distance is preferably 12-20 cm, more preferably 14-17 cm, and more preferably 15 cm; the injection rate is preferably 0.3-1 mL / h, more preferably 0.4-0.7 mL / h, and more preferably 0.6 mL / h.

[0033] In the present invention, the porosity of the base film is preferably 40-50%, more preferably 42-48%, and more preferably 45%; the pore size is preferably 200-300 nm; the thickness is preferably 20-50 μm, more preferably 30-40 μm, and more preferably 30 μm.

[0034] In the present invention, the flame retardant in the flame retardant solution preferably comprises a mixture of hexaphenoxy cyclotriphosphazene, trimethyl phosphate and nano-silicon dioxide.

[0035] In the present invention, the flame retardant in the flame retardant solution further includes zinc oxide.

[0036] In the present invention, the coating amount of the flame retardant in the coating flame retardant solution is preferably 0.5 to 2 mg / cm 2 , more preferably 1 to 1.5 mg / cm 2 , more preferably 1.2 mg / cm 2 .

[0037] In the present invention, the mass fraction of graphene oxide in the reinforcement layer solution is preferably 5-10%, more preferably 5-8%, and more preferably 5%; the mass fraction of polymer material in the reinforcement layer solution is preferably 8-15%, more preferably 10-12%, and more preferably 10%.

[0038] In the present invention, the thickness of the reinforcement film layer is preferably 10 to 20 μm, more preferably 10 to 15 μm, and even more preferably 10 μm.

[0039] In the present invention, the temperature of the hot pressing is preferably 80-150°C, more preferably 100-120°C, and more preferably 110°C; the pressure of the hot pressing is preferably 0.5-2MPa, more preferably 1-1.5MPa, and more preferably 1.3MPa; the time of the hot pressing is preferably 10-60min, more preferably 20-50min, and more preferably 30min. The present invention significantly improves the interfacial bonding strength between the flame retardant base film and the reinforcement film layer by limiting the hot pressing conditions, and the pore structure of the base film is not damaged during the hot pressing process, which is conducive to maintaining the ionic conductivity, while also improving the tensile strength and dimensional stability of the film.

[0040] The invention also provides a high-performance flame-retardant polymer electrolyte membrane prepared by a method for preparing the high-performance flame-retardant polymer electrolyte membrane.

[0041] In the present invention, the structure of the high-performance flame-retardant polymer electrolyte membrane is as follows: with the base membrane as the center, flame retardants are coated on the upper and lower surfaces of the base membrane, that is, a flame-retardant base membrane, and the upper and lower sides of the flame-retardant base membrane are reinforced by hot pressing.

[0042] The present invention also provides an application of a high-performance flame-retardant polymer electrolyte membrane in a lithium-ion battery.

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0046] (1) PVDF (molecular weight 400000-450000 g / mol) and PVA (molecular weight 100000-120000 g / mol) in a mass ratio of 7:3 were dissolved in DMF to obtain a polymer solution with a concentration of 15%; LiPF6 and [EMIM][TFSI] were added to the polymer solution, LiPF6 accounted for 20wt% of the total mass of the polymer solution, and [EMIM][TFSI] accounted for 10wt% of the total mass of the polymer solution; ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a spinning solution; the spinning solution was subjected to electrospinning, and the electrospinning conditions were: voltage of 15 kV, working distance of 15 cm, injection rate of 0.6 mL / h, to obtain a base membrane; the base membrane had a thickness of 30 μm, a porosity of 45%, and a pore size distribution between 200 and 300 nm;

[0047] (2) dissolving hexaphenoxy cyclotriphosphazene, trimethyl phosphate, and nano-silica in ethanol to obtain a flame retardant solution having a hexaphenoxy cyclotriphosphazene concentration of 1 wt %, a trimethyl phosphate concentration of 1 wt %, and a nano-silica concentration of 2 wt %; coating the flame retardant solution on the surface of the base film so that the total coating amount of the three flame retardants is 1.2 mg / cm 2 , obtaining a flame retardant base film;

[0048] (3) GO, PVDF (molecular weight 400000-450000 g / mol) and solvent DMF are mixed to obtain a reinforcement layer solution with a GO concentration of 5 wt% and a PVDF concentration of 10 wt%; the reinforcement layer solution is cast into a film to obtain a reinforcement film layer with a thickness of 10 μm;

[0049] (4) The flame retardant base film and the reinforcement film layer are hot pressed at a temperature of 110° C., a pressure of 1.3 MPa, and a time of 30 min to obtain a high-performance flame retardant polymer electrolyte membrane.

[0050] The ionic conductivity of the electrolyte membrane at room temperature was found to be 1.6×10 -3 S / cm, tensile strength of 52MPa, elongation at break of 30%, oxygen index (LOI) of 28.5%. The initial capacity of the lithium-ion battery prepared using the electrolyte membrane is 150mAh / g, and after 100 cycles, the capacity retention rate is 95%.

[0051] Example 2

[0052] This embodiment provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0053] (1) PVDF (molecular weight 400000-450000 g / mol) and PVA (molecular weight 100000-120000 g / mol) in a mass ratio of 8:2 were dissolved in DMF to obtain a polymer solution with a concentration of 12%; LiTFSI and [BMIM][TFSI] were added to the polymer solution, LiTFSI accounted for 25wt% of the total mass of the polymer solution, and [BMIM][TFSI] accounted for 15wt% of the total mass of the polymer solution; ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a spinning solution; the spinning solution was subjected to electrospinning, and the electrospinning conditions were: voltage of 16 kV, working distance of 14 cm, injection rate of 0.5 mL / h, to obtain a base membrane; the base membrane had a thickness of 35 μm, a porosity of 40%, and a pore size distribution between 200 and 300 nm;

[0054] (2) dissolving hexaphenoxy cyclotriphosphazene, trimethyl phosphate, and nano-silica in ethanol to obtain a flame retardant solution having a hexaphenoxy cyclotriphosphazene concentration of 2 wt %, a trimethyl phosphate concentration of 1 wt %, and a nano-silica concentration of 1 wt %; coating the flame retardant solution on the surface of the base film so that the total coating amount of the three flame retardants is 1.8 mg / cm 2 , obtaining a flame retardant base film;

[0055] (3) GO, PVA (molecular weight 100000-120000 g / mol) and solvent DMF are mixed to obtain a reinforcement layer solution with a GO concentration of 8 wt% and a PVA concentration of 12 wt%; the reinforcement layer solution is cast into a film to obtain a reinforcement film layer with a thickness of 15 μm;

[0056] (4) The flame retardant base film and the reinforcement film layer are hot pressed at a temperature of 120° C., a pressure of 1 MPa, and a time of 40 min to obtain a high-performance flame retardant polymer electrolyte membrane.

[0057] The ionic conductivity of the electrolyte membrane at room temperature was found to be 1.8×10 -3 S / cm, tensile strength of 55MPa, elongation at break of 32%, oxygen index (LOI) of 30.2%. The initial capacity of the lithium-ion battery prepared using the electrolyte membrane is 148mAh / g, and after 100 cycles, the capacity retention rate is 96%.

[0058] Example 3

[0059] This embodiment provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0060] (1) PVDF (molecular weight 400000-450000 g / mol) and PVA (molecular weight 100000-120000 g / mol) in a mass ratio of 6:4 were dissolved in DMF to obtain a polymer solution with a concentration of 18%; LiPF6 and [EMIM][TFSI] were added to the polymer solution, LiPF6 accounted for 30wt% of the total mass of the polymer solution, and [EMIM][TFSI] accounted for 20wt% of the total mass of the polymer solution; ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a spinning solution; the spinning solution was subjected to electrospinning, and the electrospinning conditions were: voltage of 14 kV, working distance of 16 cm, injection rate of 0.8 mL / h, to obtain a base membrane; the base membrane had a thickness of 38 μm, a porosity of 48%, and a pore size distribution between 200 and 300 nm;

[0061] (2) dissolving hexaphenoxy cyclotriphosphazene, trimethyl phosphate, and nano-silica in ethanol to obtain a flame retardant solution having a hexaphenoxy cyclotriphosphazene concentration of 1 wt %, a trimethyl phosphate concentration of 1 wt %, and a nano-silica concentration of 3 wt %; coating the flame retardant solution on the surface of the base film so that the total coating amount of the three flame retardants is 0.7 mg / cm 2 , obtaining a flame retardant base film;

[0062] (3) GO, PVA (molecular weight 100000-120000 g / mol) and solvent DMF were mixed to obtain a reinforcement layer solution with a GO concentration of 10 wt% and a PVA concentration of 11 wt%; the reinforcement layer solution was cast into a film to obtain a reinforcement film layer with a thickness of 12 μm;

[0063] (4) The flame retardant base film and the reinforcement film layer are hot pressed at a temperature of 120° C., a pressure of 1.5 MPa, and a time of 20 min to obtain a high-performance flame retardant polymer electrolyte membrane.

[0064] The ionic conductivity of the electrolyte membrane at room temperature was found to be 1.9×10 -3 S / cm, tensile strength of 57MPa, elongation at break of 35%, oxygen index (LOI) of 27.8%. The initial capacity of the lithium-ion battery prepared using the electrolyte membrane is 152mAh / g, and after 100 cycles, the capacity retention rate is 94%.

[0065] Example 4

[0066] This embodiment provides a method for preparing a high-performance flame-retardant polymer electrolyte membrane, comprising the following steps:

[0067] (1) PLA (molecular weight 90000-110000 g / mol) and PVA (molecular weight 100000-120000 g / mol) in a mass ratio of 7:3 were dissolved in DMF to obtain a polymer solution with a concentration of 20%; LiPF6 and [EMIM][TFSI] were added to the polymer solution, LiPF6 accounted for 20wt% of the total mass of the polymer solution, and [EMIM][TFSI] accounted for 10wt% of the total mass of the polymer solution; ultrasonic treatment was performed for 30 minutes to ensure uniform dispersion to obtain a spinning solution; the spinning solution was subjected to electrospinning, and the electrospinning conditions were: voltage of 17 kV, working distance of 15 cm, injection rate of 0.6 mL / h, to obtain a base film; the base film had a thickness of 33 μm, a porosity of 44%, and a pore size distribution between 200 and 300 nm;

[0068] (2) dissolving hexaphenoxy cyclotriphosphazene, trimethyl phosphate, nano-silica, and zinc oxide in ethanol to obtain a flame retardant solution having a hexaphenoxy cyclotriphosphazene concentration of 1 wt %, a trimethyl phosphate concentration of 1 wt %, a nano-silica concentration of 2 wt %, and a zinc oxide concentration of 1 wt %; coating the flame retardant solution on the surface of the base film so that the total coating amount of the four flame retardants is 1.6 mg / cm 2 , obtaining a flame retardant base film;

[0069] (3) GO, PLA (molecular weight 90000-110000 g / mol) and solvent DMF were mixed to obtain a reinforcement layer solution with a GO concentration of 7 wt% and a PLA concentration of 15 wt%; the reinforcement layer solution was cast into a film to obtain a reinforcement film layer with a thickness of 10 μm;

[0070] (4) The flame retardant base film and the reinforcement film layer are hot pressed at a temperature of 140° C., a pressure of 1.7 MPa, and a time of 50 min to obtain a high-performance flame retardant polymer electrolyte membrane.

[0071] The ionic conductivity of the electrolyte membrane at room temperature was 1.7×10 -3 S / cm, tensile strength of 54MPa, elongation at break of 29%, oxygen index (LOI) of 30%. The initial capacity of the lithium-ion battery prepared using the electrolyte membrane is 155mAh / g, and after 100 cycles, the capacity retention rate is 96%.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance flame-retardant polymer electrolyte membrane, characterized in that: The following steps are involved: Mixing a polymer material and a solvent to obtain a polymer solution; adding an ion conductive material to the polymer solution to obtain a spinning solution; electrospinning the spinning solution to obtain a base film; coating a flame retardant solution on the surface of the base film to obtain a flame retardant base film; Mixing graphene oxide, polymer material and solvent to obtain a reinforcement layer solution; Casting the reinforcement layer solution into a film to obtain a reinforcement film layer; The flame-retardant base film and the reinforcement film layer are hot pressed to obtain a high-performance flame-retardant polymer electrolyte membrane.

2. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 1, characterized in that: The polymer material is independently one or more of polylactic acid, polyvinyl alcohol and polyvinylidene fluoride.

3. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 2, characterized in that: The ion conductive material is a mixture of lithium salt and ionic liquid; the mass of the ion conductive material is 10-50% of the mass of the polymer solution.

4. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 3, characterized in that: The conditions for the electrospinning are: a voltage of 10 to 20 kV; a working distance of 12 to 20 cm; and an injection rate of 0.3 to 1 mL / h.

5. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 1 or 3, characterized in that: The flame retardant in the flame retardant solution includes a mixture of hexaphenoxy cyclotriphosphazene, trimethyl phosphate, and nano-silicon dioxide; the coating amount of the flame retardant in the coating flame retardant solution is 0.5-2 mg / cm 2 .

6. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 5, characterized in that: The mass fraction of graphene oxide in the reinforcement layer solution is 5-10%; the mass fraction of polymer material in the reinforcement layer solution is 8-15%.

7. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 6, characterized in that: The thickness of the reinforcement film layer is 10-20 μm.

8. The method for preparing a high-performance flame-retardant polymer electrolyte membrane according to claim 7, characterized in that: The temperature of the hot pressing is 80-150° C.; the pressure of the hot pressing is 0.5-2 MPa; and the time of the hot pressing is 10-60 min.

9. A high-performance flame-retardant polymer electrolyte membrane obtained by the method for preparing a high-performance flame-retardant polymer electrolyte membrane according to any one of claims 1 to 8.

10. Use of the high-performance flame-retardant polymer electrolyte membrane according to claim 9 in lithium-ion batteries.